Redesign of PCR primers for mitochondrial cytochrome c oxidase subunit I for marine invertebrates and application in all‐taxa biotic surveys. (13th July 2013) - Geller, J.; Meyer, C.; Parker, M.; Hawk, H.
Abstract: DNA barcoding is a powerful tool for species detection, identification and discovery. Metazoan DNA barcoding is primarily based upon a specific region of the cytochrome c oxidase subunit I gene that is PCR amplified by primers HCO2198 and LCO1490 ('Folmer primers') designed by Folmer et al . ( Molecular Marine Biology and Biotechnology, 3, 1994, 294). Analysis of sequences published since 1994 has revealed mismatches in the Folmer primers to many metazoans. These sequences also show that an extremely high level of degeneracy would be necessary in updated Folmer primers to maintain broad taxonomic utility. In primers jgHCO2198 and jgLCO1490, we replaced most fully degenerated sites with inosine nucleotides that complement all four natural nucleotides and modified other sites to better match major marine invertebrate groups. The modified primers were used to amplify and sequence cytochrome c oxidase subunit I from 9105 specimens from Moorea, French Polynesia and San Francisco Bay, California, USA representing 23 phyla, 42 classes and 121 orders. The new primers, jgHCO2198 and jgLCO1490, are well suited for routine DNA barcoding, all‐taxon surveys and metazoan metagenomics.